2007
DOI: 10.1121/1.2749450
|View full text |Cite
|
Sign up to set email alerts
|

Observations of potential acoustic cues that attract sperm whales to longline fishing in the Gulf of Alaska

Abstract: Sperm whales (Physeter macrocephalus) have learned to remove fish from demersal longline gear deployments off the eastern Gulf of Alaska, and are often observed to arrive at a site after a haul begins, suggesting a response to potential acoustic cues like fishing-gear strum, hydraulic winch tones, and propeller cavitation. Passive acoustic recorders attached to anchorlines have permitted continuous monitoring of the ambient noise environment before and during fishing hauls. Timing and tracking analyses of sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 36 publications
(26 reference statements)
0
38
0
Order By: Relevance
“…It is the largest marine mammal known to depredate on human fishing activities, and these activities have received increasing coverage in the scientific literature. [31][32][33][34][35][36][37][38][39] In 2003 the Southeast Alaska Sperm Whale Avoidance Project ͑SEASWAP͒ was established by scientists, managers, and fishermen to characterize the severity of sperm whale depredation activity on black cod ͑Anoplopoma fimbria͒ off Sitka, Alaska. Passive acoustic measurements collected during SEASWAP discovered that the animals occasionally dove below the fishing vessels at depths less than 100 m, depths presumably shallow enough to permit visual observations of this activity.…”
Section: ͒mentioning
confidence: 99%
“…It is the largest marine mammal known to depredate on human fishing activities, and these activities have received increasing coverage in the scientific literature. [31][32][33][34][35][36][37][38][39] In 2003 the Southeast Alaska Sperm Whale Avoidance Project ͑SEASWAP͒ was established by scientists, managers, and fishermen to characterize the severity of sperm whale depredation activity on black cod ͑Anoplopoma fimbria͒ off Sitka, Alaska. Passive acoustic measurements collected during SEASWAP discovered that the animals occasionally dove below the fishing vessels at depths less than 100 m, depths presumably shallow enough to permit visual observations of this activity.…”
Section: ͒mentioning
confidence: 99%
“…One key aspect of the study has been determining what acoustic cues alert the animals to fishing activity and over what distance these cues are detectable above background noise levels. Preliminary work found that whales identify demersal longline fishing hauls by the cavitation sounds generated by the engagement/disengagement of the vessels' propellers during hauling (Thode et al, 2007). However, determining the ranges over which whales respond to these cues is more problematic, as it requires an acoustic deployment for tracking whale positions over several hours while covering a region of at least 10 miles in radius.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the Southeast Alaska Sperm Whale Avoidance Project (SEASWAP) was created to quantify the scale of this depredation in the EGOA and to recommend strategies to reduce it. Passive acoustic monitoring and bioacoustic tagging became important tools for studying sperm whale behavior during natural and depredation foraging behaviors (Thode et al, 2007;Mathias et al, 2009, Mathias et al, 2012. One key aspect of the study has been determining what acoustic cues alert the animals to fishing activity and over what distance these cues are detectable above background noise levels.…”
Section: Introductionmentioning
confidence: 99%
“…In the marine environment, anthropogenic noise from fishing boat engines, pingers, sonar and acoustic deterrent devices used on fish farms could be used by predators to locate prey resulting in a 'dinner bell' effect. Marine mammals have been found to be attracted by such sounds (Chilvers & Corkeron, 2001;Thode et al, 2007), occasionally even to sounds introduced with the intention of deterring them (Bordino et al, 2002). In wild populations, higher incidences of predation at fisheries with acoustic deterrent devices (ADDs) may be attributed to learned associations between sound and prey (Jefferson & Curry, 1996).…”
Section: The Use Of Noise As a Signal For Prey Detectionmentioning
confidence: 99%